Peramalan Penjualan Semen Menggunakan Metode Single Moving Average dan Double Moving Average - Yuliana, Nur Lutfi; Santi, Nirma Ceisa; Mahmudah, Nur (JURNAL RISET KOMPUTER (JURIKOM), 2025)
UD. Kurnia Makmur is a shop that sells various building materials including cement. Previously, the shop UD. Kurnia Makmur still had difficulty in determining the amount of cement stock that should be provided, UD. Kurnia Makmur often also experiences shortages or excess stock due to the rise and fall of inconsistent market demand. Therefore, a forecasting method is needed that can help make better decisions in estimating the amount of cement stock that must be provided. The method used to predict cement stock in this study is the single moving average and double moving average methods. The purpose of this forecasting study is for the company to know the amount that must be provided according to consumer demand for cement sales and to know the accuracy between the single moving average and double moving average methods. Because the previous journal showed that both methods produced a MAPE of less than 10% where, it can be interpreted that if the MAPE is less than 10% then the forecast is very good. In calculating the accuracy of this study using MAD (Mean Absolute Percentage Error) and MAPE (Mean Absolute Percentage Error) using Microsoft Excel as the calculation tool. After being calculated using Microsoft Excel, the results obtained in the study were MAD of 30.72 and MAPE of 2.0% for the single moving average, while the double moving average produced MAD of 19.0 and MAPE of 1.24%.